The Relationship Between Serum Calprotectin Levels and Severity in Myasthenia Gravis Patients at Dr. M. Djamil Hospital Padang - Novia Riza Lestari; Lydia Susanti; Yuliarni Syafrita; Restu Susanti; Reno Bestari; Dedi Sutia (Universitas Pahlawan Tuanku Tambusai, 2026)
Myasthenia Gravis (MG) is an autoimmune disorder characterized by skeletal muscle weakness resulting from impaired neuromuscular transmission, primarily caused by autoantibodies directed against acetylcholine receptors. Excessive immune activation in MG triggers the release of inflammatory mediators, one of which is calprotectin — a protein complex of S100A8/A9 that is released by neutrophils and monocytes during the inflammatory process. Elevated levels of calprotectin have been reported in various autoimmune diseases; however, the relationship between serum calprotectin concentration and disease severity in MG, based on the Myasthenia Gravis Foundation of America (MGFA) classification, has not been extensively investigated. The objective of this study was to determine the association between serum calprotectin levels and disease severity in patients with MG. This study employed a cross-sectional design involving 23 MG patients receiving treatment at Dr. M. Djamil Hospital, Padang, from May to July 2025. Serum calprotectin levels were measured using the ELISA method, while MG severity was assessed using the MGFA scoring system. Statistical analyses were performed using SPSS version 27.0, with a significance level set at p < 0.05. The results of this study showed that serum calprotectin levels in patients with Myasthenia Gravis (MG) tended to be higher than in the healthy population; however, there was no significant association with the Myasthenia Gravis Foundation of America (MGFA) severity classification (p = 0.276).